2018
DOI: 10.1101/494633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone-Inspired Microarchitectured Materials with Enhanced Fatigue Life

Abstract: Text 2 Microarchitectured materials achieve superior mechanical properties through geometry 17 rather than composition 1-4 . Although lightweight, high-porosity microarchitectured materials can 18 have high stiffness and strength, stress concentrations within the microstructure can cause flaw 19 intolerance under cyclic loading 5,6 , limiting fatigue life. However, it is not known how 20 microarchitecture contributes to fatigue life. Naturally occurring materials can display 21 exceptional mechanical performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…However, all three of these parameters had a significant and strong correlation with bone volume fraction, and this study therefore does not constitute evidence for geometrical changes in the trabecular compartment driving mechanical properties beyond the loss of material. Fatigue failure of trabecular bone may further be related to elements oriented transversely to the main loading direction, which have little effect on stiffness and strength [49].…”
Section: Measures Of Local Shape Beyond Structure Model Index and Ellipsoid Factormentioning
confidence: 99%
See 1 more Smart Citation
“…However, all three of these parameters had a significant and strong correlation with bone volume fraction, and this study therefore does not constitute evidence for geometrical changes in the trabecular compartment driving mechanical properties beyond the loss of material. Fatigue failure of trabecular bone may further be related to elements oriented transversely to the main loading direction, which have little effect on stiffness and strength [49].…”
Section: Measures Of Local Shape Beyond Structure Model Index and Ellipsoid Factormentioning
confidence: 99%
“…On the other hand, this intentional feature of EF may be useful to detect situations where a pure change in shape (without differences bone volume fraction or local thickness) is responsible for altered mechanical properties. Torres et al [49] found that the size, shape and orientation of small off-axis members can be critical for the mechanical performance of porous materials. The maximal ellipsoids' EF, orientation and volume could provide this additional information.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Furthermore, AM is leading to novel ways of enhancing product performance such as printing of a bone-inspired architecture for substantially improving fatigue life of foam-like products. [58].…”
Section: Resultsmentioning
confidence: 99%
“…However, all three of these parameters had a significant and strong correlation with bone volume fraction, and this study therefore does not constitute evidence for geometrical changes in the trabecular compartment driving mechanical properties beyond the loss of material. Fatigue failure of trabecular bone may further be related to elements oriented transversely to the main loading direction, which have little effect on stiffness and strength [45].…”
Section: (B) Measures Of Local Shape Beyond Smi and Efmentioning
confidence: 99%